STEM Learning Environment: Perceptions and Implementation Skills in Prospective Science Teachers (Jurnal Pendidikan IPA Indonesia, 2021)
The STEM learning environment is the practice of students’ class solving problems. They use two or more STEM disciplines to solve the problem. The study aims to analyze the perceptions and implementation skills of the STEM learning environment in science education students before and after teaching internships. Perceptions and implementation skills of STEM in prospective teachers or initiatives about STEM are essential in shaping prospective teachers’ characters in facilitating their students as the 21st-century generation. This research used a qualitative approach with descriptive statistical analysis. The data had been retrieved since 2019, then in 2020 after teaching internship. The total of students in this study was 86 from the 2018 class. The students came from three Islamic State Universities in Indonesia. Data collection was carried out through interviews, surveys, and pictures of perceptions and the implementation skill of STEM. The STEM learning environment instruments used were based on integration, personal experience, realistic problems, multiple representation, collaboration, student-centered instruction, and the engineering design process. The results of this study indicated that there is a significant increase in the perception and implementation skill of the STEM learning environment in science education students after teaching internship, indicated by the result of the paired sample t-test were the Asymp Sig.α5 for each indicator. Perceptions and skills of implementing STEM learning environments in students’ science education increased from before and after the teaching internship. It shows that the curriculum of the science education study program must be designed with a STEM learning environment approach to have good teaching skills. Curriculum design that leads to increased understanding has pedagogic and professional courses, especially pedagogical courses which include strategic subjects, learning models, learning media, and learning tools.